PERANCANGAN TAMAN MANGROVE DI MULYOREJO SURABAYA DENGAN PENDEKATAN ARSITEKTUR BERKELANJUTAN - Nugraha, Yosia Kristya; Dr. Ar. Bayu Arief Firsandy, ST., M.Sc., IAI. (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2025)
Akaraya Mangrove Utopia is an architectural tourism park design responding to the issue of illegal fishpond land conversion and the lack of educational recreation facilities in East Surabaya’s coastal area. The design integrates recreational, educational, and conservation functions within an environmentally responsible approach. It adopts the Sustainable Sites Initiative (SITES) principles and architectural precedents of eco-parks and lodging, emphasizing carbon reduction, ecological resilience, and psychological well-being. Elevated structures, wooden deck pathways, and sustainable utilities are applied to minimize land disturbance. With a range of facilities including water attractions, education centers, glamping, and social spaces, Akaraya aims to become an architectural bridge between recreation, conservation, and coastal regeneration. Keywords: Mangrove, Tourism Park, Educational Tourism, Sustainable Architecture